2023
DOI: 10.3389/fmed.2023.1184392
|View full text |Cite
|
Sign up to set email alerts
|

Application of virtual simulation in clinical skills and operation courses

Abstract: AimThis study investigated the effectiveness and prospect of applying virtual simulation operation (VSO) as a novel teaching tool in clinical skill and operation courses.MethodsA comparative test and survey study on the teaching effect of VSO was conducted with the clinical skill and operation course as the test course. The test group students received offline courses combined with online VSO practice. In contrast, the control group students received offline courses combined with instructional video review. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Students who used the virtual microbiology laboratory had a greater understanding of microbiology concepts, demonstrated proficiency and better performance 2 . Virtual simulation operation was a teaching tool found effective in teaching clinical skills as well and garnered positive response from the students 48 . Immersive virtual reality could enable surgical skills acquistion comparitive to the cadaver laboratory in orthopaedic residents while significantly reducing cost 49 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Students who used the virtual microbiology laboratory had a greater understanding of microbiology concepts, demonstrated proficiency and better performance 2 . Virtual simulation operation was a teaching tool found effective in teaching clinical skills as well and garnered positive response from the students 48 . Immersive virtual reality could enable surgical skills acquistion comparitive to the cadaver laboratory in orthopaedic residents while significantly reducing cost 49 .…”
Section: Discussionmentioning
confidence: 99%
“…With familiarity, students would be able to use the VR laboratories to their maximum potential to complement their learning. While most of the feedback on VR platforms for skills training is positive, students have still indicated that they would like to practice on real patients and real animals 48 , 49 . One reason for this is the lack of a realistic feeling and engagement.…”
Section: Discussionmentioning
confidence: 99%